ASPERGILLUS GLAUCUS GROUP DAN PENICILLIUM SP DI RUANG OPERASI BEDAH SARAF - Nurul Hasanah; Nurhayana Sennang; Benny Rusli (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Nosocomial infections occur widely in the world, most of them were in the poor and developing countries, because those infectiondiseases were still the mayor cause of high morbidity and mortality. All microorganisms including fungi may cause nosocomial infection.The fungal as opportunistic pathogens can threat immunocompromised patients such as neurosurgical patients and HIV/AIDS patients.The aim of this study was to identify the fungal species found in the neurosurgery and HIV/AIDS rooms at Dr. Wahidin SudirohusodoHospital Makassar. This study was a cross sectional study. The sample was the air in neurosurgery operating theater and HIV/AIDSward collected using Micro biology Air Sampler 100. The identification of fungal species using lacto phenol cotton blue stain were done inBalai Besar Laboratorium Kesehatan Makassar in the period of June up to July 2010. The amount of fungal colonies in the neurosurgeryroom was 36 CFU/m3 and the identified fungi were Aspergillus’s glaucus group and Penicillum sp. The amount range of fungal coloniesin HIV/AIDS ward were 102–158 CFU/m3 and the identified fungi were: Aspergillus’s Niger, Aspergillus’s glaucus group and Penicilliumsp. Based on this study it can be concluded that only Aspergillus’s glaucus and Penicillium sp were found in the neurosurgery operatingtheater and HIV/AIDS ward, while Aspergillus’s Niger was only found in the HIV/AIDS ward.